Evaluations of Vertical Resolution of Conductive Polymer Three-Dimensional Microstructures Photofabricated in Transparent Polymer Sheet - Yamada, Katsumi; Kyoya, Akemi; Sone, Junji; Chen, Jun (Optical review, 2011)
Conductive polymer three-dimensional microstructures were photofabricated utilizing the two-photon absorption of a sensitizer dye. The resulting three-dimensional structures were excised from the transparent polymer sheet using a micro-manipulator. The processing precisions for the vertical direction of the conductive polymer three-dimensional microstructure obtained in the transparent polymer sheet were evaluated in the present study. As a result, for the configurations of the obtained polypyrrole line deposition, the line height/line width ratios were around 5: 1; this ratio is higher than that of other UV resin works ( h : w 2:4–3: 1) and the cross section distortion is not negligible for maintaining the higher reproducibility of the photofabrication.